Peran Strategis Farmasi dalam Sistem Pelayanan Kesehatan Modern - Yelfi Anwar; Atisi Atisi; Dewi Lestari; Dwike Ardatillah; Fiolita Etsa Aurora; Heny Prabowo; Maria Imaculada Mendonca Sarmento; Mardhiyah Fithriana Mufti; Rini Afiza; Vintha Sary Uly (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The National Webinar titled “The Strategic Role of Pharmacy in Modern Healthcare Systems” was organized to enhance participants' understanding of pharmacy's role in supporting safe, effective, efficient, and patient-oriented healthcare services. The event was held online via Zoom on June 5, 2026, and was attended by university students, pharmacy professionals, the general public, and students from Timor-Leste. Topics covered included pharmacoeconomics, social and behavioral pharmacy, pharmacoepidemiology, patient safety, interprofessional collaboration, antimicrobial stewardship, and the digitalization of pharmacy services. Evaluation was conducted using pre-tests and post-tests to measure the improvement in participants' understanding. The results showed an increase in understanding, evidenced by a rise in the percentage of participants achieving a perfect score from 50% in the pre-test to 56% in the post-test. A total of 88 participants attended, exceeding the initial target of 50. The webinar successfully broadened participants' insights into the strategic role of pharmacy within modern healthcare systems. Similar events could be organized in the future to foster competency development and improve the quality of evidence-based pharmacy services.